Comparative Efficacy and Safety of Individual SGLT2 Inhibitors (Dapagliflozin, Empagliflozin, and Canagliflozin) on Kidney Function Decline in CKD: A Systematic Review and Network Meta-Analysis - Krismeikesari Krismeikesari (Open Access Indonesian Journal of Medical Reviews, 2025)
Sodium-glucose cotransporter 2 (SGLT2) inhibitors are a cornerstone therapy for chronic kidney disease (CKD). However, direct head-to-head randomized controlled trials (RCTs) comparing individual agents are absent. We aimed to compare the relative efficacy and safety of dapagliflozin, empagliflozin, and canagliflozin on kidney function decline in CKD patients. We conducted a PRISMA-NMA compliant systematic review and Bayesian network meta-analysis (NMA). MEDLINE, Embase, and CENTRAL were searched for Phase 3 RCTs with more than 1000 participants comparing dapagliflozin, empagliflozin, or canagliflozin with placebo in adults with CKD. The primary efficacy outcome was a composite of sustained greater than or equal to 50 percent estimated GFR (eGFR) decline, end-stage kidney disease (ESKD), or renal/cardiovascular (CV) death. Nine landmark RCTs (DAPA-CKD, EMPA-KIDNEY, CREDENCE, DECLARE-TIMI 58, EMPA-REG OUTCOME, CANVAS, DAPA-HF, EMPEROR-Pooled, and DELIVER) enrolling a total of 89,452 patients were included. All agents were significantly superior to placebo. The NMA found no statistically significant evidence of superiority for any agent over another for the primary outcome: dapagliflozin vs. empagliflozin (Hazard Ratio [HR] 0.92; 95% Credible Interval [CrI] 0.81-1.06), dapagliflozin vs. canagliflozin (HR 0.94; 95% CrI 0.82-1.09), and empagliflozin vs. canagliflozin (HR 1.02; 95% CrI 0.89-1.17). These findings were robust across multiple sensitivity analyses and consistent for secondary renal and key safety outcomes, including acute kidney injury (AKI) and diabetic ketoacidosis (DKA). This comprehensive NMA found no statistically significant differences in the renoprotective efficacy or safety of dapagliflozin, empagliflozin, and canagliflozin. The findings are consistent with a potent class effect, but do not establish formal equivalence. This suggests the choice among these three agents can be guided by patient-specific co-morbidities, cost, and formulary availability rather than an assumed difference in relative kidney efficacy.